Pengembangan Literasi dan Numerasi melalui Kampus Mengajar Angkatan 2 di SD Inpres Paga - Jessi Claudia Boe (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Teaching Campus Batch 2 is one of Merdeka Campus' policies on the type of teaching activities in schools. This program invites students to contribute directly to the education of elementary and junior high school students in schools throughout Indonesia, especially in the 3 T areas (lagging, outermost, and leading). The Teaching Campus Program Batch 2, especially at the Paga Inpres Elementary School, has been going on for 5 months, from August to December 2021. The activities carried out are Knowledge Transfer, Technology Transfer and Administrative Affairs. The method used in this study is the method of habituation in the sense that students can develop literacy and numeracy in the elementary school. The final result in this study is that students can develop literacy and numeracy with activities that Campus Teaching students have done at Paga Inpres Elementary School.